Closing the Gap Between Organizational Requirements and Object Oriented Modeling - Castro, Jaelson; Alencar, Fernanda; Cysneiros, Gilberto (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2000: Anais do XIV Simpósio Brasileiro de Engenharia de Software, 2000)
Requirements Engineering has been considered a key activity in any Software Engineering process. It is well known that a requirements specification should include not only software specifications but also business models and other kinds of information describing the context in which the intended system will function. In recent years we have observed a growing influence of the object-orientation paradigm. Unfortunately, the current dominant object oriented modeling technique, i.e. Unified Modeling Technique, is ill equipped for modeling early requirements which are typically informal and often focus on Organizational objectives. UML is more suitable for later phases of requirements capture, which usually focus on completeness, consistency, and automated verification of functional requirements for the new system. In this paper, we present some guidelines for the integration of early and late requirements specifications. For the organizational modeling we use the i* framework, which focuses of the description of organizational relationships among various organizational actors, as well as an understanding of the rationale for the alternatives chosen. For the functional requirements specification, we rely on a precise subset of the Unified Modeling Language annotated with constraints described in the Object Constraint Language. A small example is used to illustrate how the requirements process iterates between the early and late requirements specification.